Evaluation of Elephant-Human Conflict Tista-Mechi Area Northern West Bengal - Roy, Mukti (Indian Forester, 2015)
Evaluation of Elephant-human conflict at Tista to River Mechi was done during the period 2000-2010. Data were gathered from various sources (Elephant Depredation Records from Forest Divisions, Ranges and Tea Gardens Association offices). Overall, 140 human death and 36 injured reported during the period of 2001-2010. Average 11.7 people’s Â±1.70/year. Kurseong (9.3 peoples/yrÂ±1.5) found more number of deaths than Baikunathpur (1.30/yrÂ±0.5) or wildlife-I (1.30/yrÂ±0.3). Human death found peak during the month June and November, which coincided crop harvesting season maize and paddy respectively. However, statistically there is significant variation found both season. However, division wise analysis gives significant variation. On an average 471.6/year house are demolished Kurseong (366.3Â±68.80 cases/year) is getting more number of house damage by elephant than Baikunthapur (85.8Â±29.68) and Wildlife-I (19.5Â±6.97). Sixty five (65) elephant deaths reported in this region (Tista- Mechi) during the period of 2000-01 to 2011-12. Out of this, elephant -human conflict related cases (54%) that include gunshot (18.5%), Iron wounds (13.8%), electrocution (15.4%), and chemical poisoning (6.2%) were recorded. Landscape level planning is needed with consolidating habitat of Baikunthapur, Wildlife-I and Kurseong Forest Division including Jhapa Forest Division Nepal. Alternative crop can be prompted at large-scale with society formation to reduce conflict level in this region.